The Role of the Environmental Service in Waste Management in Kerinci Regency - Nurdin, Ilham; Eni Kurniawati; Muchtar, Henny; Indrawadi, Junaidi; Irwan, Irwan (Jurnal Edukasi Terkini, 2024)
The background of the research is the less-than-optimal management of waste in the environmental service. The purpose of this study was to determine the role of the Environmental Service in managing waste in Kerinci Regency. This type of research is a qualitative descriptive approach, with data sourced from primary data and secondary data. We determined the informants through purposive sampling. We collected data through observation, interviews, and documentation. We analysed the data using data reduction, data display, and drew conclusions. The results of the study indicate that: The role of the environmental service in managing waste in Kerinci Regency is the expected component (Expected Role). The Environmental Service of Kerinci Regency, as the agency responsible for waste management, seeks to overcome the increase in waste volume by reducing the volume of waste from its source through community empowerment. The Environmental Service of Kerinci Regency fulfils the elements of its actual role. The Environmental Service of Kerinci Regency carries out its role in utilising waste by forming a waste bank.